Schooling, cognitive skills, and the Latin American growth puzzle - Eric Alan Hanushek; Ludger Woessmann (Institute for the Study of Labor (IZA), 2009)
Economic development in Latin America has trailed most other world regions over the past four decades despite its relatively high initial development and school attainment levels. This puzzle can be resolved by considering the actual learning as expressed in tests of cognitive skills, on which Latin American countries consistently perform at the bottom. In growth models estimated across world regions, these low levels of cognitive skills can account for the poor growth performance of Latin America. Given the limitations of worldwide tests in discriminating performance at low levels, we also introduce measures from two regional tests designed to measure performance for all Latin American countries with internationally comparable income data. Our growth analysis using these data confirms the significant effects of cognitive skills on intra-regional variations. Splicing the new regional tests into the worldwide tests, we also confirm this effect in extended worldwide regressions, although it appears somewhat smaller in the regional Latin American data than in the worldwide data.
Keywords: H4; I2; O4; N16; 330; Human capital; economic growth; cognitive skills; Latin America; Bildungsniveau; Kognition; Entwicklung; Wirtschaftswachstum; Schätzung; Lateinamerika